PERANCANGAN DASHBOARD KINERJA BERBASIS WEB DENGAN MENGGUNAKAN METODE KEY PERFORMANCE INDICATORS SEBAGAI MONITORING PERKEMBANGAN PEFORMA KARYAWAN DI AYAM GEPREK BANGSUS BEJI GUNUNG GANGSIR - Setiawan Illahi, Abdi; Muhammad Khadafi Setiyansyah, Muhammad Khadafi Setiyansyah; Wildan Mualim, Wildan Mualim; Hari Moerti, Hari Moerti (LPPM ITB Yadika Pasuruan, 2025)
Ayam Geprek Bangsus Restaurant which is the focus of the analysis of this final task review, has problems with employee performance such as work activities do not always reach the targets given by managers, less responsible for completing every job given to him, and the absence of media presentation of information with clear documentation. Because professional and responsible work is a way to get results and achievements in every company, therefore managers must pay attention and strive to guarantee and maintain employees who work in the company. With a dashboard as monitoring employee performance will make it easier for managers to get information about the development of work done by employees, Identify problems that may occur, display data and information as needed, document all employee performance monitoring activities, and predict the obstacles and risks that may be posed if the work done is not in accordance with the process, work time, and achievement targets. So that it can help the superior to make decisions about human resource performance more quickly and appropriately.